Algorithmic Authority and Public Trust: A Bibliometric Analysis of YouTube's Recommendation System in Shaping Islamic Religious Authority (2013-2023) - Samudra, Imam; Laini , Zakiyyah Wardatul; Juni yanti; Amin, Syukri; Fransiskus Novrianto Pakpahan (CV. Lenggogeni Data Publishing, 2024)
This study provides a comprehensive bibliometric analysis of the scholarly discourse on algorithmic authority and public trust concerning YouTube's recommendation system in shaping Islamic religious authority (2013-2023). Analyzing 677 Scopus-indexed documents from China, Indonesia, and Taiwan, this research employs co-citation and bibliographic coupling analyses to map the field's intellectual structure. The findings reveal a robust knowledge base anchored in studies of Islamic reformism, post-Islamism, and contemporary religious authority, while current research fronts explore the interplay of inspirational content, source credibility, and misinformation. The co-citation analysis identified key thematic clusters, including